A map of the night : poems - Wagoner, David (Illinois poetry series., 2008)
David Wagoners wide-ranging poetry buzzes and swells with life. Woods, streams, and fields fascinate him--he happily admits his devotion to Thoreau--but so do people and their habits, dear friends and family, the odd poet, and strangers who become even stranger when looked at closely. In this new collection, Wagoner catches the mixed feelings of a long drive, the sensations of walking against a current, the difficulty of writing poetry with noisily amorous neighbors, and many more uniquely familiar experiences.